Regaining Loss in Dynamic Stability after Control Surface Failure for an Air-Breathing Hypersonic Aircraft Flying At Mach 8.0 - Zaludin, Zairil A. (Asian Review of Mechanical Engineering, 2021)
The aim of the study is to reconfigure the automatic flight control systems of a hypersonic vehicle so that dynamic stability can be restored when flight control fails. LQR theory is used to first find the feedback gain when all 3 flight control systems are working. Failure was simulated one at a time to investigate lost in dynamic stability. When instability occurs, the new gains are obtained for the remaining flight controls using a modified Minimum Principal theory. The simulations show that the dynamic stability can be restored using these new reconfiguration gains if any one of the 3 flight control systems fail at one time but not in combination. The failure of elevator flaps at hypersonic speeds is likely due to aerodynamic heating. It is shown that the engine diffuser and the temperature across combustor controls can regain longitudinal dynamic stability to at least slow down the aircraft to safety. Study is limited to longitudinal motion only.